Development and validation of a predictive nomogram for postoperative osteonecrosis of the femoral head with cannulated screws fixation - Zhu, Wanbo (Ann Transl Med, 2021)
BACKGROUND: Osteonecrosis of the femoral head (ONFH) remains a major complication of femoral neck fractures. Early interventions require preliminary prediction and detection. In this study, we aimed to evaluate the perioperative variables of postoperative ONFH in femoral neck fracture patients with closed reduction and cannulated screw fixation. We also established and validated an individualized nomogram for the prediction of postoperative ONFH. METHODS: We included 470 patients with ONFH from two hospitals [First Affiliated Hospital of University of Science and Technology of China (n=360) and Southern Branch of the First Affiliated Hospital of the University of Science and Technology of China (n=110)]. We evaluated the prognostic value of multiple perioperative variables using a Cox regression model in the training cohort. We developed a nomogram for the prediction of ONFH using a logistic regression model. We assessed the performance of this nomogram in a validation cohort and evaluated its clinical value. RESULTS: Of the 470 patients who met the inclusion criteria, 141 (30.0%) developed postoperative ONFH. We found alcohol use [odds ratio (OR), 1.743, 95% confidence interval (CI), 1.042–2.901, P=0.033], cerebrovascular disease (OR, 5.357, 95% CI, 2.318–13.13, P<0.001), interval to surgery (OR, 5.273, 95% CI, 2.724–10.43, P<0.001), Garden classification (OR, 23.17, 95% CI, 6.812–145.3, P<0.001), Garden index (OR, 5.935, 95% CI, 2.670–14.184, P<0.001), interval to partial weight-bearing (OR, 0.053, 95% CI, 0.006–0.296, P=0.002), and six-month Harris hip score (OR, 0.856; 95% CI, 0.792–0.919, P<0.001) were independent predictors of postoperative development of ONFH. Based on these variables, we developed a nomogram that showed good discrimination in both the training [area under the curve (AUC) =0.865] and the validation cohort (AUC =0.877). The favorable performance of this nomogram was also confirmed in the validation cohort. CONCLUSIONS: We developed and validated an easy-to-use nomogram for predicting postoperative ONFH. This nomogram can aid decision-making of intraoperative interventions and postoperative rehabilitation plans for patients, surgeons, and osteo-rehabilitative physicians.